Study of Knowledge and Sexual Behavior in the Prevention of HIV/ AIDS in Non-Professional Personnel in Kendal District - Triana Arisdiani; Hendra Adi Prasetya (Global Health Science Group, 2021)
HIV/ AIDS cases are an iceberg phenomenon with a much less reported number than the facts. A number of data reports that non-professional personnel are one of the highest contributors to the number of HIV/ AIDS cases in Indonesia. Objective: The purpose of this study was to describe sexual knowledge and behavior in the prevention of HIV/ AIDS among non-professional personnel in Kendal Regency. In this study, researchers used quantitative research methods using descriptive survey research design. The research sample consisted of 85 people with a purposive sampling technique. The results of this study indicate that the majority of non-professionals have good knowledge of HIV/ AIDS (58.8%) but their behavior falls into the category of risky sexual behavior (71.8%). The conclusion of this study that the majority of respondents had a good level of knowledge of HIV/ AIDS and had risky sexual behavior.